Man's World? Political Masculinities in Literature and Culture - Sauer, Birgit 1957- (Cambridge Scholars Publishing, 2014)
Political institutions and practices such as the state, parliament, citizenship and nationality, the vote, the military, and the making and implementation of laws have traditionally been treated as if they were un-gendered and guided exclusively by objective reasoning and rationality. Rationality and reason, though, have been habitually ascribed to masculinity, a fact which has often been ignored in favour of the apparent gender-inclusiveness of the realm of politics. In contrast to this view, this book explores the interdependence of the construction of masculinities, on the one hand, and the emerging, maintenance, and modification of concepts such as the state, citizenship, nationality and nationalism, democracy and militarism on the other. Illustrating the great amount of research activity in the field of political masculinities, the book offers many perspectives in its attempt to shed light on different modes of representing and constructing political masculinities across time and space. Findings from the fields of political science, history, media studies, literature, and film studies, as well as cultural studies, encourage an interdisciplinary debate of political masculinities in Europe and the United States from the nineteenth to the twenty-first century